Some fixed point theorems on non-convex sets - Mohanasundaram Radhakrishnan; S. Rajesh; Sushama Agrawal (Applied General Topology, 2017)
In this paper, we prove that if $K$ is a nonempty weakly compact set in a Banach space $X$, $T:K→ K$ is a nonexpansive map satisfying $\frac{x+Tx}{2}\in K$ for all $x\in K$ and if $X$ is $3-$uniformly convex or $X$ has the Opial property, then $T$ has a fixed point in $K.$